Release of Sureties - Sethu, R.R. (Journal of Malaysian and Comparative Law, 2019)
The perennial problem with the application and interpretation of the Contracts Act has always been the extent to which English decisions and English principles may be resorted to. Though the long title to the Act says it is to "define" and "amend" the law of contract it does not say in what respects and what law it defines and in what respect of what law it amends. It has always been thought, despite the absolute of lack of mention in the text, that it adopts with modifications in some instances the rules of English law.